Recommendations of the Brazilian Society of Rheumatology for the use of JAK inhibitors in the management of rheumatoid arthritis - Karina Rossi Bonfiglioli; Licia Maria Henrique da Mota; Ana Cristina de Medeiros Ribeiro; Adriana Maria Kakehasi; Ieda Maria Magalhães Laurindo; Rina Dalva Neubarth Giorgi; Angela Luzia Branco Pinto Duarte; Ana Paula Monteiro Gomides Reis; Mariana Peixoto Guimarães Ubirajara e Silva de Souza; Claiton Viegas Brenol; Geraldo da Rocha Castelar Pinheiro; Cleandro Pires de Albuquerque; et al. (Advances in Rheumatology, 2021)
Abstract Rheumatoid arthritis (RA) is a chronic and autoimmune systemic inflammatory disease that can cause irreversible joint deformities, with increased morbidity and mortality and a significant impact on the quality of life of the affected individual. The main objective of RA treatment is to achieve sustained clinical remission or low disease activity. However, up to 40% of patients do not respond to available treatments, including bDMARDs. New therapeutic targets for RA are emerging, such as Janus kinases (JAKs). These are essential for intracellular signaling (via JAK-STAT) in response to many cytokines involved in RA immunopathogenesis. JAK inhibitors (JAKi) have established themselves as a highly effective treatment, gaining increasing space in the therapeutic arsenal for the treatment of RA. The current recommendations aim to present a review of the main aspects related to the efficacy and safety of JAKis in RA patients, and to update the recommendations and treatment algorithm proposed by the Brazilian Society of Rheumatology in 2017.